The inevitability of linguistic change: The motivation of borrowing English terms by Shona speakers - Lettiah Gumbo; Davie E Mutasa (Taylor and Francis Group, 2023)
Europeans brought new concepts, ideas and technologies with them that had not existed before colonialism in Zimbabwe. This led Shona and other indigenous languages (such as Ndebele, Venda, Nambya, Kalanga) to absorb a substantial new vocabulary into their lexicons. Speakers of these languages have been creating terms to cope with the new concepts through various strategies. This article aims at studying the motivation of Shona speakers to prefer borrowed words where both Shona and the English terms are available. Results of the research for this study show that Shona speakers seem to prefer English loanwords owing to issues such as prestige and elitism, shortness and precision, explicitness, expressiveness, currency of term, gap-filling and language modernisation. In addition, an unfavourable language policy in Zimbabwe helps to promote the use of English in all spheres of life, thereby undermining the development of Shona. This study is qualitative in nature, and it adopts a descriptive approach in analysing the data gathered through structured and oral interviews, questionnaires and secondary sources. The major contribution of this study is the illustration of how borrowing can be used to benefit the indigenous language development initiatives and to help language policy planners in Zimbabwe.